Impact of New Education Policy 2020 on Educational System of India: Examining the Impact of NEP 2020 on Higher Education (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The New Education Policy declared by Government of India (NEP 2020) was an inviting change and new news in the midst of the multitude of negativities encompassing the world because of the difficulties presented by Covid19 pandemic. The declaration of NEP 2020 was absolutely unforeseen by many. The progressions that NEP 2020 has suggested were something that numerous educationists never saw coming. However the education policy has impacted school and school education similarly, this article mostly centers around NEP 2020 and its impact on Higher Education. This paper likewise traces the striking elements of NEP and investigations what they mean for the current education system.